Marketing Ethics and Customer Loyalty: The Serial Mediating Role of Relationship Quality and the Moderating Role of Voluntary Simplicity - Abdulaziz Sezer; Abdulvahap Baydaş (Interdisciplinary Description of Complex Systems)
Although there has been considerable theoretical support outlining a relationship between marketing ethics and customer loyalty, there is limited empirical evidence validating this relationship. This study examines the relationships among perceptions of marketing ethics and customer loyalty in a sample of Turkish consumers. The results demonstrate that marketing ethics is negatively related to customer loyalty. Furthermore, this research investigates the processes through which marketing ethics affects customer loyalty. The relationship between marketing ethics and customer loyalty is sequentially mediated by customer satisfaction and customer trust. On the other hand, this research also investigates whether voluntary simplicity has a moderating role in the impact of marketing ethics on customer satisfaction and customer trust. The results demonstrate that the relationship between marketing ethics and customer satisfaction is moderated by self-sufficiency and intangible life which are sub-dimensions of voluntary simplicity; however, there is no moderating role of planned shopping and simplicity in product which are the other sub-dimensions of voluntary simplicity.